Formation of creative librarians as a factor of readiness to innovations - I. V. Dombrovskaya (Библиосфера)
The method and the effectiveness of implementation of a new training program for library staff are considered. The results of experimental study showing that the development of creativity is a factor in readiness for innovation are described.